ONSITE TRIAGE, PRE-HOSPITAL MANAGEMENT AND EFFECTIVE HOSPITAL TRANSPORTATION WHERE DO WE STAND? - Muzzammil, Muhammad; Minhas, Muhammad Saeed; Khan, Anser Saeed; Effendi, Jahazeb; Minhas, Muhammad Owais; Jabbar, Saadia (Journal of Ayub Medical College Abbottabad, 2021)
Background: To improve morbidity and mortality outcomes in mass casualty victims it is pertinent that a system of prehospital triage be implemented. The objectives of this study are to determine the knowledge, attitude and practices of emergency care transporters and ambulance personnel towards onsite triage, pre-hospital management and transportation to hospital of critically injured and wounded patients in mass casualty incidents and other emergencies in Karachi, Pakistan. Method: All ambulance personnel and emergency care transporters who transported patients to the hospital were included in the study. Pre-tested questionnaire was self-administered after obtaining written consent. Results: Among 250 emergency care transporters (ambulance personnel), mostly belonged to age group 21-25 years 73 (29.2%). Most of emergency transport provider teams were composed of only 1 person who was the driver of ambulance 22 (80%) and only 44 (17.6%) had the facility of paramedics. Regarding lifesaving equipment facilities in ambulance, 188 (75.2%) ambulances did not have these and only 62 (24.8%) were equipped. Predominantly, the ambulance personnel performed the '˜scoop and run' practice and the ambulance works as a transport vehicle 188(75.2%), while facilities of basic life support were available in only 45 (18%) and advance life support facility in 17 (6.8%). Among all 203 (81.2%) did not think they are able to decide who is severely injured and 183(73.2%) believe they are unable to do triage in mass causalities. Conclusion: Our study showed significant gaps in the knowledge of the emergency care providers regarding triage of patients especially in mass casualty incidents. Though the response time and time to the hospital center is comparable, no pre-hospital lifesaving interventions are attempted en-route. A coordinated effort by the ambulance services, hospitals and the government are detrimental for a swift functioning of a trauma system.